Clinical outcomes of carbon ion radiotherapy for locally advanced adenocarcinoma of the uterine cervix in phase 1/2 clinical trial (protocol 9704). Issue 11 (3rd March 2014) - Wakatsuki, Masaru; Kato, Shingo; Ohno, Tatsuya; Karasawa, Kumiko; Kiyohara, Hiroki; Tamaki, Tomoaki; Ando, Ken; Tsujii, Hirohiko; Nakano, Takashi; Kamada, Tadashi; Shozu, Makio; The Working Group of the Gynecological Tumor
<x xml:space="preserve">Abstract</x> BACKGROUND This study sought to evaluate the toxicity and efficacy of carbon ion radiotherapy (C‐ion RT) for locally advanced adenocarcinoma of the uterine cervix in a phase 1/2 clinical trial. METHODS The treatment consisted of whole‐pelvic irradiation of 36.0 gray equivalents (GyE) in 12 fractions and local boost with dose escalation from 26.4 to 38.4 GyE in 8 fractions. The dose escalation was performed with careful observation of acute normal tissue responses. Total dose to the cervical tumor was 62.4 to 74.4 GyE in 20 fractions. RESULTS Between April 1998 and February 2010, 58 patients were treated with C‐ion RT in this clinical trial. The number of patients with stage IIB, IIIB, and IVA disease were 20, 35, and 3, respectively. Median tumor size was 5.5 cm (range, 3.0‐11.8 cm). Twenty‐seven patients had pelvic lymph node metastases. The median follow‐up period was 38 months. All patients completed the treatment schedule. Grade 2 or higher late toxicity was found in 8 patients: 5 with bladder and 2 with small intestine grade 2 toxicities, and 1 patient had grade 4 rectal complication, which was surgically salvaged. The 5‐year local control rate, local control rate including salvage surgery, and overall survival rate in all cases were 54.5%, 68.2%, and 38.1%, respectively. CONCLUSIONS Dose escalation of C‐ion RT for adenocarcinoma of the uterine cervix was accomplished without severe toxicities except in 1 case. Although the number of patients in this study was small, the results support continued investigation and analysis to confirm therapeutic efficacy. Cancer 2014;120:1663–1669. © 2014 American Cancer Society.